Leptin into the ventrolateral medulla facilitates chemorespiratory response in leptin‐deficient (ob/ob) mice. (13th March 2014) - Bassi, M.; Furuya, W. I.; Menani, J. V.; Colombari, D. S. A.; do Carmo, J. M.; da Silva, A. A.; Hall, J. E.; Moreira, T. S.; Wenker, I. C.; Mulkey, D. K.; Colombari, E.
Abstract Aim Leptin, an adipocyte‐derived hormone, is suggested to participate in the central control of breathing. We hypothesized that leptin may facilitate ventilatory responses to chemoreflex activation by acting on respiratory nuclei of the ventrolateral medulla. The baseline ventilation and the ventilatory responses to CO2 were evaluated before and after daily injections of leptin into the retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG) for 3 days in obese leptin‐deficient (ob/ob) mice. Methods Male ob/ob mice (40–45 g, n = 7 per group) received daily microinjections of vehicle or leptin (1 μg per 100 nL) for 3 days into the RTN/pFRG. Respiratory responses to CO2 were measured by whole‐body plethysmography. Results Unilateral microinjection of leptin into the RTN/pFRG in ob/ob mice increased baseline ventilation (VE) from 1447 ± 96 to 2405 ±174 mL min−1 kg−1 by increasing tidal volume (VT) from 6.4 ± 0.4 to 9.1 ± 0.8 mL kg−1 (P < 0.05). Leptin also enhanced ventilatory responses to 7% CO2 (Δ = 2172 ± 218 mL min−1 kg−1, vs. control: Δ = 1255 ± 105 mL min−1 kg−1), which was also due to increased VT (Δ = 4.71 ± 0.51 mL kg−1, vs. control: Δ = 2.27 ± 0.20 mL kg−1), without changes in respiratory frequency. Leptin treatment into the RTN/pFRG or into the surrounding areas decreased food intake (83 and 70%, respectively), without significantly changing body weight. Conclusion The present results suggest that leptin acting in the respiratory nuclei of the ventrolateral medulla improves baseline VE and VT and facilitates respiratory responses to hypercapnia in ob/ob mice.